Controlling Pulse-Like Self-Sustained Oscillators Using Analog Circuits and Microcontrollers - Domguia, Ulrich Simo; Siewe, Raoul Thepi (International Journal of Robotics and Control Systems, 2023)
Using simulation from analog electronic circuits and from a microcontroller, this paper considers the control or synchronization of pulse-like self-sustained oscillators described by the equations derived from the chemical system known as Brusselator. The attention is focused on the effect of proportional control when the Brusselator is subjected to disturbances such as pulse-like oscillations and square signals. The analog electronic circuits simulation is based on Multisim, while the microcontroller simulation uses mikroC software and PIC 18F4550. In order to determine the intervals for which the synchronization is effective, the equations of the Brusselator are solved numerically using the fourth-order Runge-Kutta method. As software used for conducting numerical simulations, FORTRAN 95 version PLATO is used for numerical simulation and MATLAB for plotting curves using the data generated from FORTRAN simulations. It has been shown that the control is effective for some values of the proportional control parameter. A good qualitative and quantitative agreement is found from the results of the numerical simulation and those obtained from the analog electronic circuits as well as those delivered by the microcontroller. Since the oscillations delivered by the heart are pulsed oscillations, this study gives an idea of how to control the heart frequency of an individual whose heart is subject to certain disturbances related to stress or illness, to name just a few examples.